Ganglioneurofibroma arising within the extralobar pulmonary sequestration - Liu, Yuanyuan (J Cardiothorac Surg, 2020)
BACKGROUND: Neurogenic tumor arising within the pulmonary sequestration (PS) is rare. CASE PRESENTATION: A 42-year-old asymptomatic female was referred to our hospital for work-up of extralobar PS. The independent feeding artery from the thoracic aorta was confirmed by three-dimensional computed tomography angiography (3D-CTA). Uniportal thoracoscopic resection of the sequestrated lung with mediastinal lymph node sampling was performed successfully. Ganglioneurofibroma within the PS was diagnosed as the specimen revealed positive expression of SRY-related HMG-box 10 protein, neuron-specific enolase, S-100, chromogranin A and synuclein. Tumor recurrence was not recorded 1 year after the surgery. CONCLUSION: Preoperative 3D-CTA is useful to identify the aberrant vessels of PS. An elaborate diagnostic work-up after a timely resection is necessary for subsequent management and follow-up plan.